Hypovitaminosis D and risk factors in pediatric epilepsy children - Napakjira Likasitthananon; Charcrin Nabangchang; Thitiwan Simasathien; Suchavadee Vichutavate; Voraluck Phatarakijnirund; Piradee Suwanpakdee (BMC, 2021)
Abstract Background Anti-seizure medication (ASM) treatment is one of the significant risk factors associated with abnormal vitamin D status in epilepsy patients. Multiple studies have shown that adult epilepsy patients can exhibit vitamin D deficiency. However, there are few reports investigating pediatric epilepsy patients. In this study, we aimed to identify risk factors related to hypovitaminosis D in pediatric epilepsy patients in Thailand. Methods A cross-sectional retrospective cohort study was conducted in 138 pediatric epilepsy patients who received anticonvulsants from April 2018 to January 2019. Demographic data, seizure types, puberty status, physical activity, duration, and types of anti-seizure medications were analyzed. Patients with abnormal liver function, abnormal renal function, and who received vitamin D supplements or ketogenic diet containing vitamin D were excluded. Levels of serum vitamin D (25(OH)D) were measured. Results All 138 subjects were enrolled, the age ranged from 1.04 - 19.96 years; (mean = 9.65 ± 5.09), the mean serum 25(OH) D level was 26.56 ± 9.67 ng/ml. The prevalence of vitamin D deficiency was 23.2% and insufficiency was 47.8% respectively. Two risk factors-puberty status (OR 5.43, 95% CI 1.879-15.67) and non-enzyme-inhibiting ASMs therapy (OR 3.58, 95% CI 1.117-11.46)-were significantly associated with hypovitaminosis D, as shown by multivariate analyses. Conclusions Our study reports the high prevalence of hypovitaminosis D in pediatric epilepsy patients in Thailand despite being located in the tropical zone. These findings can guide clinicians to measure vitamin D status in pediatric epilepsy patients particularly when they reach puberty and/or are using non-enzyme-inhibiting ASMs therapy. Early detection of vitamin D status and prompt vitamin D supplementation can prevent fractures and osteoporosis later in life. Trial registration TCTR20210215005 ( http://www.clinicaltrials.in.th/ ).